Sliding balloon-assisted thrombectomy combined with aspiration and intrasinus urokinase thrombolysis for the treatment of hemorrhagic cerebral venous sinus thrombosis: experience of 10 patients - Zhang, Mingsi; Jiang, Feixin; Wen, Qingyan; Chen, Yiman; Zhang, Zhiquan; Zhang, Min; Zhong, Jianxin (Frontiers in Neurology, 2025)
BackgroundCerebral venous sinus thrombosis (CVST) is an unusual cause of stroke. Currently, standard anticoagulant therapy does not have satisfactory efficacy for treating some cases of hemorrhagic CVST. Therefore, we explored the efficacy and safety of the combination of sliding balloon-assisted thrombectomy with aspiration and intrasinus urokinase thrombolysis for the treatment of CVST patients with intracranial hemorrhage (ICH).MethodsWe retrospectively analyzed the clinical, imaging and follow-up data of 10 CVST patients with ICH who underwent sliding balloon-assisted thrombectomy combined with aspiration and intrasinus thrombolysis with urokinase from February 2022 to June 2023. Complete recanalization and partial recanalization in the cerebral venous sinus were defined as imaging outcomes, and the modified Rankin score (mRS) at the 3-month and 6-month follow-ups was used to evaluate clinical efficacy.ResultsA total of 10 CVST patients aged 18–68 years were enrolled, including 5 males. All of the patients was diagnosed with ICH by noncontrast CT and with thrombosis at 3 or more venous sinuses by digital subtraction angiography (DSA). After treatment, complete recanalization was achieved in 6 patients, and partial recanalization was achieved in 4 patients. At the 3- and 6-month follow-up, all 10 patients showed neurological independence (mRS score ≤ 2), without any signs of symptom aggravation, cerebral hematoma enlargement, pulmonary embolism or other complications after treatment.ConclusionThese results indicated that the combination of sliding balloon-assisted thrombectomy, aspiration and intrasinus urokinase thrombolysis may be safe and effective for the treatment of CVST patients with intracranial hemorrhage.